2023
DOI: 10.1186/s12968-023-00915-2
|View full text |Cite
|
Sign up to set email alerts
|

Reverse remodeling of left atrium assessed by cardiovascular magnetic resonance feature tracking in hypertrophic obstructive cardiomyopathy after septal myectomy

Abstract: Background Assessing the structure and function of left atrium (LA) is crucial in hypertrophic obstructive cardiomyopathy (HOCM) because LA remodeling correlates with atrial fibrillation. However, few studies have investigated the potential effect of myomectomy on LA phasic remodeling in HOCM after myectomy using cardiovascular magnetic resonance (CMR) feature tracking (FT). This study aims to evaluate the LA structural and functional remodeling with HOCM after myectomy by CMR-FT and to further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Cardiac CT is highly valuable and versatile tool which could identify the components of outflow tract obstruction and apical aneurysm [ 63 ]. MRI showed LA reverse remodeling in HOCM patients after septal myectomy, which displayed a reduction in LA size and a restoration in LA reservoir and function, but unchanged LA conduit function [ 64 ]. However, myocardial fibrosis was increased after myectomy in the one-year follow-up, which is observed by late gadolinium enhancement in the left ventricle [ 65 ].…”
Section: Cardiac Surgical Diseasesmentioning
confidence: 99%
“…Cardiac CT is highly valuable and versatile tool which could identify the components of outflow tract obstruction and apical aneurysm [ 63 ]. MRI showed LA reverse remodeling in HOCM patients after septal myectomy, which displayed a reduction in LA size and a restoration in LA reservoir and function, but unchanged LA conduit function [ 64 ]. However, myocardial fibrosis was increased after myectomy in the one-year follow-up, which is observed by late gadolinium enhancement in the left ventricle [ 65 ].…”
Section: Cardiac Surgical Diseasesmentioning
confidence: 99%
“…Cardiac magnetic resonance (CMR)-derived feature-tracking technology enables visualization and quanti cation of myocardial strain [15]. Several studies that used CMR-Tagging as a reference standard have shown the good reproducibility of this technique [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with T2DM and AR show an increase in LV end-diastolic volume (LVEDV) and pressure, affecting the LA function and aggravating the LV function [13]. Patients with T2DM alone and those with T2DM with mitral regurgitation exhibit decreased LA strain [14].However, there have been few studies on impaired LA strain and atrioventricular coupling in patients with T2DM and AR.Cardiac magnetic resonance (CMR)-derived feature-tracking technology enables visualization and quanti cation of myocardial strain [15]. Several studies that used CMR-Tagging as a reference standard have shown the good reproducibility of this technique [16,17].…”
mentioning
confidence: 99%